Cardiovascular response to exercise in elite ice hockey players - Bossone, E.; Vriz, O.; Bodini, B. D.; Rubenfire, M. (Canadian Journal of Cardiology, 2004)
BACKGROUND: High-performance ice hockey requires unique strength and endurance, which are facilitated by training.